ANALISIS PENANAMAN NILAI - NILAI SOSIAL OLEH ORANGTUA PADA ANAK USIASEKOLAH DI DESAPENITI BESAR - Mahardika Erin Saputra; Izhar Salim; Supriadi Supriadi (Universitas Tanjungpura, 2019)
AbstractThis research aims to study the Analysis of Social Value Planting by Parents in School Age Children in Peniti Besar Village, Segedong District. In this study the method used is qualitative descriptive analysis. parents and school-age children of eight people were taken as samples. Data collection tools are using observation guidelines, interview guidelines, and study documentation. Planting social values instilled by parents is a material value, Pananaman material value of something useful for the body, in this material value includes two aspects, namely meeting the needs of children's clothing such as clothes, pants and others, and meet the nutritional needs of children like giving healthy and nutritious food like vegetables, meat, and fruits. Vital values, which are vital values that are instilled by parents related to everything that is useful for humans or children to carry out activities by facilitating children and spiritual values, in instilling spiritual values in school-age children have been carried out by their parents telling their children to prayers and there are also told their children to follow the recitation around his residence.Keywords: Social Value Cultivation, Parents of School Age Children.